2023
DOI: 10.1192/bjo.2023.501
|View full text |Cite|
|
Sign up to set email alerts
|

Homelessness and associated factors over a 13-year period among psychiatric in-patients in Berlin, Germany: routine data analysis

Dario Jalilzadeh Masah,
Meryam Schouler-Ocak,
Stefan Gutwinski
et al.

Abstract: Background Homeless patients in psychiatric hospitals are a scarcely studied and there is lack of knowledge about factors associated with homelessness and in-patient treatment. Aims To determine the change over time in the number of homeless psychiatric in-patients and to examine factors associated with homelessness. Method Retrospective data analysis of 1205 selected electronic patient files on psychiatric in-patient treatment in a university psychiatric hospital in Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Fazel’s ( 8 ) systematic review and meta-regression analysis, drawing on data from 5684 homeless individuals, reported the prevalence of PD among the homeless in Western countries as 23.1% (CI 15.5%–30.8%). Similar data were observed in a population of 500 homeless patients in Portugal ( 13 ) and in Germany ( 14 ) both at 24%. While in Stockholm, a prevalence of 12% was reported in 1704 homeless patients receiving hospital care ( 15 ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Fazel’s ( 8 ) systematic review and meta-regression analysis, drawing on data from 5684 homeless individuals, reported the prevalence of PD among the homeless in Western countries as 23.1% (CI 15.5%–30.8%). Similar data were observed in a population of 500 homeless patients in Portugal ( 13 ) and in Germany ( 14 ) both at 24%. While in Stockholm, a prevalence of 12% was reported in 1704 homeless patients receiving hospital care ( 15 ).…”
Section: Resultssupporting
confidence: 84%
“…Homeless people with multiple diagnoses have greater mental health needs and worse general health determinants ( 9 , 13 ). A general synthesis of the prevalence of comorbid psychiatric disorders in homeless patients, according to reports reveals the following figures: psychotic disorders among 4.4%–57% ( 8 , 13 , 14 , 16 ); major depression among 11.4% ( 8 ); bipolar disorders among 11.4%–17.5% ( 8 , 16 ); alcohol dependence among 14.3%–37.9% ( 8 , 13 , 14 , 16 ); drug dependence among 14.3%–34% ( 8 , 13 , 14 , 16 ); acute stress reaction among 23%–24% ( 13 , 14 ); and anxiety disorder among 2.3% ( 16 ). These references are based on studies carried out in the USA, France, Japan, Portugal, and Germany.…”
Section: Resultsmentioning
confidence: 99%